Uji Pemberian Volume Air Melalui Sistem Irigasi Tetes Pada Pembibitan Utama (Main nursery) Kelapa Sawit (Elaeis guineensis Jacq) - Nababan, Judika; Manurung, Gulat M E; ', Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research is to determine the appropriate water volume application during the growth of oil palm ( Elaeis guineensis Jacq ) in the main nursery by a drip irrigation system. This research has been conducted in the Agriculture Experimental Station Faculty of Agriculture, University of Riau, District of Tampan, the research was carried out for 4 months starting in July 2013 to the month of November 2013 utilized completely randomized design ( CRD ) with four treatments of water volume A1, A2, A3, and A4 ( 100 % of 3 liters of water, 75 % of 3 liters of water, 50 % from 3 liters of water. and 25 % from 3 liters of water ). The results of this research are plant height increament oil palm seedlings, increament the number of leaves of palm seedlings, seed weevil accretion wrap palm, coconut root volume mustard seeds, palm seeds dry weight, and water content of the soil additional parameters. The data obtained were analyzed using the analysis of variance and proceed with further testing DNMRT at 5% level. The results suggest giving 100 % of the water volume from 3 liters of water increase influence on plant height, girth increase tuber, root volume, plant dry weight, and water content in the soil, while the provision of 100 % of the water volume of 3 liters of water indicates that the influence is not significant on the number of leaves. Keywords: water volume, Main nursery and oil palm (Elaeis guineensis Jacq)